2018
DOI: 10.1186/s12885-018-5146-3
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II study on cisplatin, pemetrexed, and bevacizumab followed by maintenance with pemetrexed and bevacizumab for patients with advanced or recurrent nonsquamous non-small cell lung cancer: MAP study

Abstract: BackgroundWe evaluated the safety and efficacy of induction chemotherapy with bevacizumab followed by maintenance chemotherapy with bevacizumab for advanced non-small cell lung cancer (NSCLC) in this multicenter phase II study.MethodsChemotherapy-naïve patient with stage IIIB–IV or recurrent nonsquamous NSCLC were eligible. We planned approximately four cycles of induction cisplatin (75 mg/m2), pemetrexed (500 mg/m2), and bevacizumab (15 mg/kg) followed by maintenance with pemetrexed (500 mg/m2) and bevacizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Many clinical trials of anti-VEGF drugs have shown that patients receiving anti-VEGF drugs had higher rates of GI perforation than those without such treatment [ [21] , [22] , [23] , [24] , [25] ]. Several authors have further reported that the risk of emergency surgery due to anti-VEGF agent-related severe adverse effects in advanced cancer was estimated to be as high as 2.8% [ 23 , [26] , [27] , [28] , [29] ]. Other authors reported that the fatality rate of patients with GI perforation treated with anti-VEGF drugs was as high as 20% [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials of anti-VEGF drugs have shown that patients receiving anti-VEGF drugs had higher rates of GI perforation than those without such treatment [ [21] , [22] , [23] , [24] , [25] ]. Several authors have further reported that the risk of emergency surgery due to anti-VEGF agent-related severe adverse effects in advanced cancer was estimated to be as high as 2.8% [ 23 , [26] , [27] , [28] , [29] ]. Other authors reported that the fatality rate of patients with GI perforation treated with anti-VEGF drugs was as high as 20% [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expected mPFS of 7.5 months was not reached in this study. Nevertheless, anlotinib plus chemotherapy induced fewer TRAEs, especially grade 3–4 TRAEs, compared with bevacizumab plus chemotherapy 18 …”
Section: Discussionmentioning
confidence: 94%
“…The mPFS of platinum plus pemetrexed was 4.5 months, as mentioned above, and combining anlotinib with platinum and pemetrexed showed an improved mPFS of 5.75 months in this study. Bevacizumab plus platinum and pemetrexed were reported to achieve even better mPFS (7.4–10.8 months), 17 , 18 and the use of pemetrexed in the maintenance treatment might be an explanation. In this study, only anlotinib was used in the maintenance treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the JMDB study, PC was the preferred chemotherapy regimen for non-small cell lung cancer ( Scagliotti et al, 2008 ). Moreover, many studies demonstrated that the combination of bevacizumab with PC was well tolerated in the treatment of NSCLC ( Barlesi et al, 2013 ; Patel et al, 2013 ; Zinner et al, 2015 ; Xu et al, 2016 ; Shan et al, 2018 ; Tsutani et al, 2018 ; Kreis et al, 2019 ). We conducted the assessment of treatment with real world study to compare the efficacy and safety of low (7.5 mg/kg) and high (15 mg/kg) dose of bevacizumab in combination with PC in advanced non-squamous NSCLC.…”
Section: Introductionmentioning
confidence: 99%